Carcinogenesis of nasopharyngeal carcinoma: an alternate hypothetical mechanism. Issue 1 (6th January 2016) - Poh, Sharon Shuxian; Chua, Melvin Lee Kiang; Wee, Joseph T. S.
Abstract: Current proposed mechanisms implicate both early and latent Epstein–Barr virus (EBV) infection in the carcinogenic cascade, whereas epidemiological studies have always associated nasopharyngeal carcinoma (NPC) with early childhood EBV infection and with chronic ear, nose, and sinus conditions. Moreover, most patients with NPC present with IgA antibody titers to EBV capsid antigen (VCA‐IgA), which can precede actual tumor presentation by several years. If early childhood EBV infection indeed constitutes a key event in NPC carcinogenesis, one would have to explain the inability to detect the virus in normal nasopharyngeal epithelium of patients at a high risk for EBV infection. It is perhaps possible that EBV resides within the salivary glands, instead of the epithelium, during latency. This claim is indirectly supported by observations that the East Asian phenotype shares the characteristics of an increased susceptibility to NPC and immature salivary gland morphogenesis, the latter of which is influenced by the association of salivary gland morphogenesis with an evolutionary variant of the human ectodysplasin receptor gene ( EDAR ), EDARV370A . Whether the immature salivary gland represents a more favorable nidus for EBV is uncertain, but in patients with infectious mononucleosis, EBV has been isolated in this anatomical organ. The presence of EBV‐induced lymphoepitheliomas in the salivary glands and lungs further addresses the possibility of submucosal spread of the virus. Adding to the fact that the fossa of Rosen Müller contains a transformative zone active only in the first decade of life, one might be tempted to speculate the possibility of an alternative carcinogenic cascade for NPC that is perhaps not dissimilar to the model of human papillomavirus and cervical cancer.